2002
DOI: 10.2307/3087429
|View full text |Cite
|
Sign up to set email alerts
|

Structural Estimation of the Affiliated Private Value Auction Model

Abstract: price sealed-bid auctions. The model allows for bidders' individual efficiencies and opportunity costs, while permitting dependence among bidders' private values through affiliation. We establish the nonparametric identification of the APV model, characterize its theoretical restrictions, and propose a computationally convenient and consistent two-step nonparametric estimation procedure for estimating the joint private value distribution from observed bids. Using simulated bid data we provide a step by step gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 30 publications
5
91
0
1
Order By: Relevance
“…Moreover, CIPV can rationalize a sample of bids if and only if the inverse-bid function is monotonic. As in Li et al (2002), the power of this last result lies in the fact that their estimation procedure allows for verification of monotonicity, which in turn implies that the CIPV assumption is partially testable (subject, of course, to other sources of model misspecification).…”
Section: Conditionally Independent Private Informationmentioning
confidence: 87%
See 4 more Smart Citations
“…Moreover, CIPV can rationalize a sample of bids if and only if the inverse-bid function is monotonic. As in Li et al (2002), the power of this last result lies in the fact that their estimation procedure allows for verification of monotonicity, which in turn implies that the CIPV assumption is partially testable (subject, of course, to other sources of model misspecification).…”
Section: Conditionally Independent Private Informationmentioning
confidence: 87%
“…The authors showed their estimator of the joint density of private values achieves the optimal uniform rate of convergence for a two-step nonparametric estimatorà la GPV-that is, the joint density of private values can be estimated at the same rate as the marginal density of private values. The copula parameterization allows for this asymptotic gain as the dimension of the joint density of private values is reduced to one which avoids the curse of dimensionality problem concerning the number of bidders and associated with the nonparametric approach of Li et al (2002). The extra copula-related work in the first step appears to pay dividends in small samples: they used Monte Carlo experiments to show their estimator is on par with GPV when data are independent and that their estimator performs well on affiliated data, even if the researcher chooses the wrong copula.…”
Section: Affiliated Private Valuesmentioning
confidence: 99%
See 3 more Smart Citations